2021
DOI: 10.3390/vaccines9060663
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Vaccination against COVID-19 in Breastfeeding Health Workers

Abstract: Background: Initially, there were no data on the safety of COVID-19 vaccines in lactating women. The aim of our study was to evaluate the immune response to COVID-19 vaccinations in breastfeeding women. Methods: The study included 32 breastfeeding women who, regardless of the study, had decided to be vaccinated. Maternal serum and breast milk samples were simultaneously collected on days 8 ± 1, 22 ± 2, 29 ± 3, and 43 ± 4 after the first dose of the vaccine. The immune response was assessed by determining the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…These differences in the timing of measurements might explain the differences in our findings, compared to other studies ( 32 , 35 ). Although we did not measure maternal blood IgA, other studies have shown that blood and milk IgA levels correlate when measured 7-10 days after the 2nd dose ( 13 , 36 ). The relationship between infant age, breastfeeding exclusivity, milk IgA antibodies, and optimal timing of vaccination during lactation remains to be studied in detail.…”
Section: Discussionmentioning
confidence: 91%
“…These differences in the timing of measurements might explain the differences in our findings, compared to other studies ( 32 , 35 ). Although we did not measure maternal blood IgA, other studies have shown that blood and milk IgA levels correlate when measured 7-10 days after the 2nd dose ( 13 , 36 ). The relationship between infant age, breastfeeding exclusivity, milk IgA antibodies, and optimal timing of vaccination during lactation remains to be studied in detail.…”
Section: Discussionmentioning
confidence: 91%
“…Antibodies that target the viral receptor binding domain (RBD) in the S1 domain of the SARS-CoV-2 spike protein have been shown to exhibit a virus-neutralizing capacity [ 64 , 65 , 144 ]. After vaccination, the highest concentrations of serum and breast milk antibodies were observed with maximum about 29 days after the second dose [ 145 ].…”
Section: Vaccinationmentioning
confidence: 99%
“…This limitation is present not only in studies of mothers who have passed the infection, but also in those in which the breast milk of mothers vaccinated against SARS-CoV-2 has been analysed, and it is also mentioned that additional studies are needed to evaluate the effect of these vaccines on lactation outcomes and infant health because the protection they may provide to the child has not been studied [ 82 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%